2019
DOI: 10.1182/blood-2018-08-869156
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral serotonin causes dengue virus–induced thrombocytopenia through 5HT2 receptors

Abstract: Dengue virus (DENV) is the most prevalent vector-borne viral pathogen, infecting millions of patients annually. Thrombocytopenia, a reduction in circulating platelet counts, is the most consistent sign of DENV-induced disease, independent of disease severity. However, the mechanisms leading to DENV-induced thrombocytopenia are unknown. Here, we show that thrombocytopenia is caused by serotonin derived from mast cells (MCs), which are immune cells that are present in the perivascular space and are a major perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…5HT2A: Few studies also present 5-hydroxytryptamine 2A receptor (commonly known as serotonin or 5HT2A receptor) as a mediator of platelet responses to infections. 5HT2A receptor is a GPCR widely known to regulate platelet physiology [ 178 ]. Due to the significant role of serotonin in regulation of the central nervous system, a major portion of the studies involving 5HT2A is focused on psychological disorders and few studies have reported the immunoregulatory functions of serotonin [ 178 ].…”
Section: Platelets Express Several Other Receptors Involved In Infmentioning
confidence: 99%
See 4 more Smart Citations
“…5HT2A: Few studies also present 5-hydroxytryptamine 2A receptor (commonly known as serotonin or 5HT2A receptor) as a mediator of platelet responses to infections. 5HT2A receptor is a GPCR widely known to regulate platelet physiology [ 178 ]. Due to the significant role of serotonin in regulation of the central nervous system, a major portion of the studies involving 5HT2A is focused on psychological disorders and few studies have reported the immunoregulatory functions of serotonin [ 178 ].…”
Section: Platelets Express Several Other Receptors Involved In Infmentioning
confidence: 99%
“…5HT2A receptor is a GPCR widely known to regulate platelet physiology [ 178 ]. Due to the significant role of serotonin in regulation of the central nervous system, a major portion of the studies involving 5HT2A is focused on psychological disorders and few studies have reported the immunoregulatory functions of serotonin [ 178 ]. Recently, it was shown that serotonin generated from mast cells during dengue infections acts on platelets through 5HT2A receptor, leading to their activation and aggregation with eventual thrombocytopenia [ 178 ].…”
Section: Platelets Express Several Other Receptors Involved In Infmentioning
confidence: 99%
See 3 more Smart Citations